﻿Limited evidence for learning in a shuttle box paradigm in crickets (Acheta domesticus) - Kiri Li N. Stauch (Pensoft Publishers, 2021)
Aversive learning has been studied in a variety of species, such as honey bees, mice, and non-human primates. Since aversive learning has been found in some invertebrates and mammals, it will be interesting to know if this ability is shared with crickets. This paper provides data on aversive learning in male and female house crickets (Acheta domesticus) using a shuttle box apparatus. Crickets are an ideal subject for these experiments due to their well-documented learning abilities in other contexts and their readily quantifiable behaviors. The shuttle box involves a two-compartment shock grid in which a ‘master’ cricket can learn to avoid the shock by moving to specific designated locations, while a paired yoked cricket is shocked regardless of its location and therefore cannot learn. Baseline control crickets were placed in the same device as the experimental crickets but did not receive a shock. Male and female master crickets demonstrated some aversive learning, as indicated by spending more time than expected by chance in the correct (no shock) location during some parts of the experiment, although there was high variability in performance. These results suggest that there is limited evidence that the house crickets in this experiment learned how to avoid the shock. Further research with additional stimuli and other cricket species should be conducted to determine if house crickets and other species of crickets exhibit aversive learning.